Comparison of Outcome of Open Hemorrhoidectomy with or without Lateral Internal Sphincterotomy (Medical Forum Monthly, 2024)
Objective: To compare the outcome of open hemorrhoidectomy with or without lateral internal sphincterotomy with regard to postoperative complications.Study Design: Comparative study.Place and Duration of Study: This study was conducted at the Surgical Department, PMCH Nawabshah from January 2018 to January 2019.Materials and Methods: All the patients were admitted through surgical OPD. Digital rectal examination along with proctoscopy was done to rule out other surgical ano-rectal pathologies. All the required investigations were done and open hemorroidectomy was done.Results: This study was conducted on 100 patients. They were divided into two groups. Group A included 50(50%) patients and Group B included 50 (50%). Group A underwent only open hemorroidectomy without LIS whereas Group B underwent LIS apart from open Hemorrhoidectomy. Postoperative pain was seen in 20% of patients in Group A whereas it was only 10% in Group B. less hospital stay and early return to work was found in Group B patients.Conclusion: It is concluded that the open hemorrhoidectomy with LIS is the better option as compared to without LIS keeping in view the outcome of both procedures.